Effect of salmon calcitonin on bone mineral density of patients with osteoporotic vertebral compression fractures (鲑降钙素对骨质疏松椎体压缩性骨折患者骨密度的影响) - CAO Min (曹敏); CHEN Siling (陈思伶); LI Na (李娜); JI Tian (纪甜); YANG Yan (杨燕); YANG Liyun (杨丽云); JIAN Huiqing (蹇会清) (中西医结合护理)
Objective To investigate the effect of salmon calcitonin on bone mineral density (BMD)of patients with osteoporotic vertebral compression fractures (OVCFs). Methods Totally 50 OVCFs were divided into the study group and control group, with 25 cases in each group. The control group received routine antiosteoporosis therapy(Teriparatide and Chinese medicine capsules for osteoporosis), and the study group was given salmon calcitonin combined with Chinese medicine capsules for osteoporosis. The alkaline phosphatase (ALP), serum calcium (S-Ca), BMD, JOA score and treatment effect of two groups were compared. Results Patients in the study group achieved better outcomes of ALP, S-Ca) BMD and JOA score compared with those in the control group(P<0. 05). The total effective rate in the study group was higher than that in the control group(P<0. 05). Conclusion By increasing the BMD and improve the functional disorder, the salmon calcitonin is effective in the treatment OVCFs. (目的 探讨鲑降钙素对骨质疏松性椎体压缩性骨折(OVCFs)患者骨密度(BMD)影响。方法 选取2020年7月—2021年7月收治的50例OVCFs患者, 分为研究组和对照组, 各25例。对照组给予常规抗骨质疏松治疗(特立帕肽+中药制剂抗骨质疏松胶囊), 研究组给予鲑降钙素联合中药制剂抗骨质疏松胶囊。观察两组干预前后碱性磷酸酶(ALP)水平、血钙(S-Ca)水平、BMD水平、JOA评分, 比较两组临床疗效。结果 干预后, 两组ALP、S-Ca、BMD和JOA评分均有改善, 且研究组优于对照组, 差异有统计学意义(P<0. 05)。研究组临床总有效率高于对照组, 差异有统计学意义(P<0. 05)。结论 鲑降钙素治疗OVCFs有良好效果, 有助于提高患者骨密度, 改善功能障碍。)